2013
DOI: 10.1038/leu.2013.193
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient stromal support in MDS results from molecular and functional deficits of mesenchymal stromal cells

Abstract: Ineffective hematopoiesis is a major characteristic of myelodysplastic syndromes (MDS) causing relevant morbidity and mortality. Mesenchymal stromal cells (MSC) have been shown to physiologically support hematopoiesis, but their contribution to the pathogenesis of MDS remains elusive. We show that MSC from patients across all MDS subtypes (n=106) exhibit significantly reduced growth and proliferative capacities accompanied by premature replicative senescence. Osteogenic differentiation was significantly reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
266
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(309 citation statements)
references
References 53 publications
25
266
3
3
Order By: Relevance
“…However difficulties in duplicating the pathological features of the disease by simple transplantation of hematopoietic stem cells to immunodefficient mice models have highlighted the involvement of the abnormal marrow microenvironment in the disease origin and progression with pivotal yet unexplained role for marrow stroma [14,15]. Research data also supports the view that abnormal microenvironment selectively supports the expansion of the malignant clone through altered signaling between diseased HSCs and malfunctioning MSCs [16][17][18][19][20][21]. Impaired capacity of MSCs to support normal hematopoiesis in MDS is attributed to abnormal signaling, altered interactions with the hematopoietic cells, altered proliferative and differentiation potential, changes in epigenetic regulation and abnormalities in cytokine secretion [16][17][18][19][20][21].…”
Section: The Role Of Bone Marrow Stroma and Mesenchymal Stem Cells Insupporting
confidence: 58%
See 3 more Smart Citations
“…However difficulties in duplicating the pathological features of the disease by simple transplantation of hematopoietic stem cells to immunodefficient mice models have highlighted the involvement of the abnormal marrow microenvironment in the disease origin and progression with pivotal yet unexplained role for marrow stroma [14,15]. Research data also supports the view that abnormal microenvironment selectively supports the expansion of the malignant clone through altered signaling between diseased HSCs and malfunctioning MSCs [16][17][18][19][20][21]. Impaired capacity of MSCs to support normal hematopoiesis in MDS is attributed to abnormal signaling, altered interactions with the hematopoietic cells, altered proliferative and differentiation potential, changes in epigenetic regulation and abnormalities in cytokine secretion [16][17][18][19][20][21].…”
Section: The Role Of Bone Marrow Stroma and Mesenchymal Stem Cells Insupporting
confidence: 58%
“…Research data also supports the view that abnormal microenvironment selectively supports the expansion of the malignant clone through altered signaling between diseased HSCs and malfunctioning MSCs [16][17][18][19][20][21]. Impaired capacity of MSCs to support normal hematopoiesis in MDS is attributed to abnormal signaling, altered interactions with the hematopoietic cells, altered proliferative and differentiation potential, changes in epigenetic regulation and abnormalities in cytokine secretion [16][17][18][19][20][21]. Gene expression analyses of MDS derived MSCs have shown altered RNA levels in both canonical and non-canonical WNT signaling pathways and is thought to be associated with impaired proliferative potential of MDS derived MSCs [20].…”
Section: The Role Of Bone Marrow Stroma and Mesenchymal Stem Cells Insupporting
confidence: 50%
See 2 more Smart Citations
“…We have recently demonstrated that mesenchymal stromal cells from patients with MDS and AML are aberrantly methylated [60][61][62]. Along with this, Verma et al showed that Aza might mediate at least some of its efficacy via demethylation of the BM stroma [3].…”
Section: Mode Of Actionmentioning
confidence: 98%